2013
DOI: 10.4269/ajtmh.13-0208
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic Survey of Epidemic Cholera in Haiti to Assess Spectrum of Illness and Risk Factors for Severe Disease

Abstract: To assess the spectrum of illness from toxigenic Vibrio cholerae O1 and risk factors for severe cholera in Haiti, we conducted a cross-sectional survey in a rural commune with more than 21,000 residents. During March 22–April 6, 2011, we interviewed 2,622 residents ≥ 2 years of age and tested serum specimens from 2,527 (96%) participants for vibriocidal and antibodies against cholera toxin; 18% of participants reported a cholera diagnosis, 39% had vibriocidal titers ≥ 320, and 64% had vibriocidal titers ≥ 80, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 30 publications
1
45
2
1
Order By: Relevance
“…However, HIV disease did not prove to be a risk factor for a trend toward more severe dehydration. One study suggested that HIV-infected patients were more susceptible to disease based on lower vibriocidal responses to cholera vaccine when compared with non-HIV infected recipients 23. In our cohort, HIV-status did not influence the severity of disease, but the HIV seroprevalence was high.…”
Section: Discussioncontrasting
confidence: 49%
“…However, HIV disease did not prove to be a risk factor for a trend toward more severe dehydration. One study suggested that HIV-infected patients were more susceptible to disease based on lower vibriocidal responses to cholera vaccine when compared with non-HIV infected recipients 23. In our cohort, HIV-status did not influence the severity of disease, but the HIV seroprevalence was high.…”
Section: Discussioncontrasting
confidence: 49%
“…The outbreak strain in Hispaniola exhibits characteristics of both the El Tor and classical biotypes,13 and it was difficult to anticipate overall attack rates or the overall proportion of Vibrio cholerae infections that might lead to severe disease in the immunologically naive population of Haiti. A seroepidemiologic survey confirmed very high rates of infection—often subclinical 14. This survey and evaluations of case series helped identify risk factors for disease.…”
mentioning
confidence: 87%
“…Un paciente falleció. El espectro de la enfermedad en este brote difiere del observado en los brotes notificados en el Caribe 12 . Justo después de esta identificación, la epidemia se extendió a los Estados de México, Hidalgo, San Luis Potosí y Veracruz.…”
Section: Definición De Casos E Identificación Bioquímicaunclassified